2012
DOI: 10.1103/physrevc.85.044914
|View full text |Cite
|
Sign up to set email alerts
|

Local multiplicity fluctuations as a signature of critical hadronization in heavy-ion collisions at TeV energies

Abstract: In central Pb-Pb collisions at LHC the multiplicity of particles produced is so high that it should become feasible to examine the nature of transition from the deconfined quark-gluon state to the confined hadron state by methods that rely on the availability of high multiplicity events. We consider four classes of the transition process ranging from critical behavior to totally random behavior, depending on whether or not there is clustering of quarks and on whether or not there is contraction of dense cluste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…7are essentially independent of the nature of the GL parameters. Such a behaviour was experimentally observed in the study of photon number fluctuations of a single-mode laser at the threshold of lasing [52,55], confirming that it is a phase transition problem describable by GL theory [56]. On the theoretical side, it has also been found that using 2-dimensional Ising model to simulate quark-hadron phase transition and the resulting scaling behaviour of F q is in agreement with Eqs.…”
Section: Scaling Exponentsupporting
confidence: 73%
See 3 more Smart Citations
“…7are essentially independent of the nature of the GL parameters. Such a behaviour was experimentally observed in the study of photon number fluctuations of a single-mode laser at the threshold of lasing [52,55], confirming that it is a phase transition problem describable by GL theory [56]. On the theoretical side, it has also been found that using 2-dimensional Ising model to simulate quark-hadron phase transition and the resulting scaling behaviour of F q is in agreement with Eqs.…”
Section: Scaling Exponentsupporting
confidence: 73%
“…The scaling exponent can be used to investigate the presence of second-order phase transition in the hadronization process in high energy nuclear interactions. Hwa and Yang [52] have reviewed many papers on local behaviours of multiplicity fluctuations of the systems undergoing a second-order phase transition describable by the Ginzburg-Landau theory. These are then connected to the distribution of clusters produced that can be used to simulate initial configurations before start of hadronization.…”
Section: Scaling Exponentmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the study of fluctuations has become an important tool in envisaging the process of phase transition in relativistic nuclear interactions [16]. A great deal of work [17][18][19][20][21][22][23] has been carried out in this field over a wide range of energies. Earlier, it has been suggested [24] that the deconfinement should result in the non-monotonous trends in the behavior of multiplicity fluctuations, which could act as an indicator for the observance of the critical point [25].…”
Section: Introductionmentioning
confidence: 99%